The Yorkshire Dales : North and East : the Howgill Fells, Mallerstang, Swaledale, Wensleydale and Nidderdale /: the Howgill Fells, Mallerstang, Swaledale, Wensleydale and Nidderdale. ([2012?]) - Kelsall, Dennis; Kelsall, Jan
No abstract available